2023
DOI: 10.3390/brainsci13060937
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Specificity of the Brentano Illusion Test in the Detection of Visual Hemi-Field Deficits in Patients with Unilateral Spatial Neglect

Maria De Luca,
Matteo Baroncini,
Alessandro Matano
et al.

Abstract: Stroke survivors with right-brain damage (RBD) often present with attentional deficits such as left unilateral spatial neglect. Some patients also present with contralesional visual hemi-field deficits. A late detection of visual hemi-field deficits (VHFD) contributes to hampering neurorehabilitation and functional outcome of patients with neglect. The Brentano Illusion Test (BRIT) may be used for an early detection of VHFD during the neuropsychological assessment. In the present study, we determined the sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…The analysis of inter-rater reliability showed that different professionals' observations of the same subject were consistent, promoting interdisciplinary collaboration and a multidisciplinary approach to patient care. The sensitivity and specificity of the FLASH were reported as 81% and 77%, respectively, which aligns with previous studies on qualitative examinations such as the confrontation method of visual field tests [28,29]. The sensitivity and specificity values are known to depend on the type, density, and cause of the visual field defect, as well as the specific confrontation method employed.…”
Section: Discussionsupporting
confidence: 86%
“…The analysis of inter-rater reliability showed that different professionals' observations of the same subject were consistent, promoting interdisciplinary collaboration and a multidisciplinary approach to patient care. The sensitivity and specificity of the FLASH were reported as 81% and 77%, respectively, which aligns with previous studies on qualitative examinations such as the confrontation method of visual field tests [28,29]. The sensitivity and specificity values are known to depend on the type, density, and cause of the visual field defect, as well as the specific confrontation method employed.…”
Section: Discussionsupporting
confidence: 86%
“…Seventy-three consecutive inpatients with acquired RBD (largely overlapping—75%—the sample described in [ 32 ]), referred for routine assessment following a stroke in the right-hemisphere, participated in the study. Inclusion criteria were as follows: age ≥ 18 years; a (haemorrhagic or ischaemic) lesion following a stroke in the right hemisphere (determined based on neuroimaging data).…”
Section: Methodsmentioning
confidence: 99%
“…The comprehensive list of tests can be found in the Supplementary Methods. The cut-offs used to classify participants into patients with neglect (N+) and without neglect (N−) can be found in [32]. As a result of the neglect battery, there were Three patients showed the presence of a deficit on this test.…”
Section: Participantsmentioning
confidence: 99%